A ditadura militar retratada nos livros didáticos de história do Brasil de 1964 a 1985 - Assunção, Cristina Adelina de (2009)
The main objective of the present paper is the analysis of the textbooks of Brazil's History written during the years of the dictatorship in order and to verify whether there is any correspondence between its pages and the precepts of the Ideology of National Security introduced by the new order, as well other voices that might exist. It has the purpose to take into consideration the way these texts portrayed its contemporaneity, since this was an adverse moment in our Republic. Therefore the texts being examined are those written between 1964 and 1985, which comprehended João Goulart's government, Military Coup and presidents-generals' administration. For this purpose, the textbooks themselves were used along with a specific bibliography concerning educational laws that were in force that period, the history of school discipline and the history of this editorial field, which analyzes not only the texts but also the school curriculum established by the Secretary of Education and its members, including authors, editorial staff and sales department. Concluding, it makes an analysis its relation with state organs responsible for the production of this, material, as illustrates the committees created by several governments that were in charge of its evaluation and subsequent distribution to public schools. During these 20 years of editorial production, it's possible to verify that changes in the national political conjuncture had repercussions on the textbooks because of the inspection of organs instituted to infiltrate into several places. One can observe that, as a consequence of the political openness, these texts were profoundly modified